2015
DOI: 10.1111/bcp.12636
|View full text |Cite
|
Sign up to set email alerts
|

Protein binding characteristics and pharmacokinetics of ceftriaxone in intensive care unit patients

Abstract: AIMSThe aim of the present study was to assess the pharmacokinetics of total and unbound ceftriaxone in intensive care unit (ICU) patients and its protein binding characteristics. METHODSTwenty patients (m/f 15/5, age 25-86 years, body weight 60-121 kg, APACHE II 7-40, estimated glomerular filtration rate 19-157 ml min -1 , albumin 11.7-30.1 g l -1 , total bilirubin <0.1-36.1 mg dl -1 ) treated with intravenous ceftriaxone were recruited from two ICUs. Timed plasma samples were obtained using an opportunistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
48
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 30 publications
11
48
4
1
Order By: Relevance
“…As for pharmacokinetics, a dose-dependent effect of alteplase on stroke outcome has been shown in different studies with significant higher rates of ICH rate with doses above 0.95 mg/kg, which has led to a licensed dose for administration of 0.9 mg/kg body weight [16]. The drug is predominantly metabolized by the liver and is eliminated via urine [16], as is ceftriaxone [17]. However, to date no data comparing both pharmacokinetic profiles have been published.…”
Section: Discussionmentioning
confidence: 99%
“…As for pharmacokinetics, a dose-dependent effect of alteplase on stroke outcome has been shown in different studies with significant higher rates of ICH rate with doses above 0.95 mg/kg, which has led to a licensed dose for administration of 0.9 mg/kg body weight [16]. The drug is predominantly metabolized by the liver and is eliminated via urine [16], as is ceftriaxone [17]. However, to date no data comparing both pharmacokinetic profiles have been published.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with healthy volunteers, the unbound fraction in our group was significantly higher (14-43% vs 5-15%) (370), but lower than other published data on critically ill patients (23% vs 33%) (369). Higher unbound concentration was seen in our patients with hyperbilirubinaemia and diabetes, which is in agreement with previous studies (369,371), however, we did not find a correlation between hypoalbuminaemia and unbound fraction. The lower CL and V dss seen in our group may have provided an explanation for the high fC 720 observed.…”
Section: Discussionsupporting
confidence: 88%
“…A dramatically lower V dss was observed in our subjects when compared with other published data on critically ill patients (10.4 vs 20.2, 20.0 L) (368,369). When compared with healthy volunteers, the unbound fraction in our group was significantly higher (14-43% vs 5-15%) (370), but lower than other published data on critically ill patients (23% vs 33%) (369).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Studies in ICU septic patients have shown very high variability in the main PK parameters of CTX, with changes in renal clearance representing the main cause [11]. No data is reported concerning increased elimination of CTX due to loss of GFB perm-selectivity.…”
Section: Introductionmentioning
confidence: 99%